A207 SCLEROSING CHOLANGITIS SECONDARY TO DISSEMINATED VARICELLA ZOSTER VIRUS: A CASE REPORT. (1st March 2018) - Charette, J; Mohamed, R; Andrews, C N; Vaughan, S; Larios, O; Jayakumar, S
Abstract: Background: Sclerosing cholangitis represents a spectrum of chronic and progressive diseases of the intrahepatic and extrahepatic biliary ducts. The condition is characterized by multifocal inflammation, fibrosis, and stricturing, resulting in biliary cirrhosis and eventual hepatic failure. While PSC accounts for the majority of cases, a small proportion can arise secondary to known causes including biliary surgery, obstruction, malignancy, bacterial cholangitis, trauma, ischemia, and infiltrative diseases. Aims: Here we present a case of sclerosing cholangitis secondary to disseminated Varicella Zoster Virus. Methods: A 70-year old female on Rituximab therapy for follicular lymphoma presented with abdominal pain, anorexia and a diffuse vesicular rash. EGD revealed severe esophagitis and a large, erosive mass in the fundus of the stomach. PCR studies of the skin and gastric mucosa confirmed the presence of disseminated Varicella Zoster Virus, which was treated with IV acyclovir. The patient presented soon after discharge with new symptoms of pruritus and fatigue, with elevated cholestatic liver enzymes. MRCP revealed multifocal strictures throughout the intrahepatic bile ducts with mild extrahepatic duct involvement. Liver biopsy was suggestive of a cholangiopathy of uncertain etiology without the classic "onion skin" pattern of PSC. Biopsies were negative for malignancy, and for viral PCR and immune serologic tests, including for autoimmune cholangiopathy. The patient showed improvement in both her symptoms and liver enzymes and repeat liver biopsy and MRCP confirmed stable disease. An endoscopic ultrasound revealed the presence of multifocal stricturing of the pancreatic duct with a normal common bile duct free of stones or sludge and normal pancreatic parenchyma. Results: The diagnosis of disseminated VZV with GI involvement, and strong temporal relationship between the appearance of biliary disease and VZV infection suggest a VZV-induced SSC. The patient showed symptomatic and biochemical improvement following treatment with acyclovir. There are many features of this presentation including the patient's age, gender, rapid onset, and clinical improvement, which are very atypical for PSC. The patient does not have a history of inflammatory bowel disease and all autoimmune markers are negative. The pancreatic duct strictures are suggestive of a secondary cause affecting both the hepatic bile ducts and pancreatic duct. There was no evidence to suggest that another known secondary cause could have contributed to this patient's presentation. Serial liver biopsies were repeatedly negative for lymphoma. Obstructive and ischemic causes of SSC were ruled out via ERCP and MRCP. Conclusions: In this case the most likely etiology of the sclerosing cholangitis is the disseminated VZV. This is the first reported case of VZV-induced SSC. Funding Agencies: None